Flexural and fracture mechanical properties of in situ particulate reinforced organomineral hybrid resins modified by organofunctional silanes. (12th April 2019) - Kopietz, Mark; Wetzel, Bernd; Friedrich, Klaus
Abstract: Mixtures of (poly)isocyanate and water glass (WG) result in water-in-oil emulsions. After an indirect two-step reaction a thermosetting organomineral hybrid resin is obtained. Crosslinked polyurea serves as the organic part, while cavitated non-bonded polysilicate particles in micron-size serve as the mineral (inorganic) part. In this work three different types of silane-terminated polymers (STP) were tested as modifiers in different concentrations of 0–10 vol%. Connection of the organic and inorganic part with improved flexural properties and fracture toughness of novel 2P hybrid resins was targeted to enhance the life-time of components made out of these materials. It was shown that all types of STP increase the processing viscosity and positively impact the (fracture) mechanical properties in different dimensions, depending on the tested modifier and its applied concentration. Compared to the unmodified 2P hybrid resin the most suitable modifiers lead in maximum to an up to three times enhanced fracture toughness as well as an increase of flexural stiffness, strength and strain to failure of about 27%, 41% and 105%, respectively. SEM analysis of fracture surfaces proofed the building of connecting bridges between the organic and inorganic part for two of the three modifiers.